Oral Hygiene Practices Among Cricketers in Chennai - BABU J D, MONESH; GANAPATHY, DHANRAJ; SASANKA, KEERTHI (The journal of contemporary issues in business and government, 2020)
Oral hygiene refers to the practice of keeping the mouth, teeth and gums clean and healthy to prevent oral disease. Oral hygiene is often taken for granted but it is essential part of our daily life.Oral hygiene is the practice of maintaining a clean oral cavity to prevent dental diseases such as dental cavities, gingivitis, periodontitis and bad breath. A total of 150 cricketers were involved in the study . Self administered questionnaire related to the oral hygiene practices along with sociodemographic details was prepared and it was distributed through an online survey link. Based on hypotonic and isotonic content of the sports drink , the majority of the participants(58.7%) prefer isotonic sports drinks and the remaining participants( 41.3%) prefer Hypotonic .About 58% of participants eat chocolate regularly. 54.6% of participants agreed that dental erosion affects oral health . 56% of participants think oral health has an impact on sports performance. In the present study, the knowledge,attitude and practice of oral hygiene is moderate.For further improvement, awareness about maintaining good oral health should be created among the public. Erosion can be prevented by educating the subjects about the risks associated with carbonated drinks which is more common among sportsmen and young adults.